1981
DOI: 10.1152/jappl.1981.51.5.1232
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic mechanisms of training bradycardia: beta-adrenergic receptors in humans

Abstract: To address the autonomic mechanisms underlying the bradycardia of physical training in human subjects, we performed a cross-sectional study comparing the heart-rate responses to graded doses of isoproterenol in 7 elite marathon runners and 7 age-matched controls, and a longitudinal study in 12 normal volunteers of the effects of 6 wk of intense physical training on lymphocyte beta-adrenergic receptors identified by l-[3H]dihydroalprenolol. We observed no significant differences between marathoners and controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 0 publications
1
14
0
1
Order By: Relevance
“…These parameters were also not changed in longitudinal studies as normal volunteers exercised (Williams et al 1981). …”
Section: Discussionmentioning
confidence: 90%
“…These parameters were also not changed in longitudinal studies as normal volunteers exercised (Williams et al 1981). …”
Section: Discussionmentioning
confidence: 90%
“…However, several other studies have failed to demonstrate differences in vagal tone between trained and untrained subjects (6,32,36,37). Yet, others have indicated a decrease in sympathetic activity in the sinus node (38) or both an increase in vagal activity and a decrease in sympathetic activity (39). On the other hand, studies on animals (33) and on humans (6,32,36,40) have suggested that this bradycardia is mainly due to a reduction in intrinsic HR.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining relations between aging and the other variables of Figures 1 and 2 were described earlier. 8 Although increased physiological sensitivity to catecholamines results from aerobic training, details of this adaptation are not completely clear; that is, whereas R. S. Williams, Eden, Moll, Lester, and Wallace (1981) found increased beta-receptor sensitivity in only skeletal (not heart) muscle after aerobic training in human subjects and R. S. Williams, Caron, and Daniel (1984) found similar results in rats, others have found heart sensitivity increases. Even sympathetic nervous system nerve fi ber densities have been increased in the hearts of rats trained by running throughout their adult lives, in comparison with untrained rats (Alho, Koistinaho, Kovanen, Suominen, & Hervonen, 1984).…”
Section: Research Confi Rmation Of the Modelmentioning
confidence: 99%